2019
DOI: 10.1590/s1677-5538.ibju.2018.0196
|View full text |Cite
|
Sign up to set email alerts
|

Impact of time from biopsy to surgery on complications, functional and oncologic outcomes following radical prostatectomy

Abstract: Introduction:To determine the impact of time from biopsy to surgery on outcomes following radical prostatectomy (RP) as the optimal interval between prostate biopsy and RP is unknown.Material and methods:We identified 7, 350 men who underwent RP at our institution between 1994 and 2012 and had a prostate biopsy within one year of surgery. Patients were grouped into five time intervals for analysis: ≤ 3 weeks, 4-6 weeks, 7-12 weeks, 12-26 weeks, and > 26 weeks. Oncologic outcomes were stratified by NCCN disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…Other studies using biochemical recurrence as the end point found 3 to 6 months as a cutoff point. 31,32 There were similar findings for patients considering radiation therapy, where they had a higher likelihood of PSA failure with high risk disease after a 2.5-month period, similar to the outcomes for surgical delay. 33 Other studies have suggested that it is possible to delay surgery for longer periods of time.…”
Section: Prostate Cancersupporting
confidence: 55%
“…Other studies using biochemical recurrence as the end point found 3 to 6 months as a cutoff point. 31,32 There were similar findings for patients considering radiation therapy, where they had a higher likelihood of PSA failure with high risk disease after a 2.5-month period, similar to the outcomes for surgical delay. 33 Other studies have suggested that it is possible to delay surgery for longer periods of time.…”
Section: Prostate Cancersupporting
confidence: 55%
“…While the majority of oncologic surgeries have maintained priority worldwide, most urologic associations have recommended to defer prostate cancer (PCa) surgeries [2][3][4]. This is based on several retrospective studies reporting the absence of poor oncologic results for PCa no matter the delay between diagnosis and surgery, although high-risk patients could be potentially at risk of higher risk of biochemical recurrence when the surgery was delayed [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…However, most available studies investigating this topic reported no significant influence of delayed prostatectomy on oncological outcomes (5,7,11,12,17,23). For example, Morini et al recently published a study examining the impact in patients with localized prostate cancer reporting no correlation in timefrom-biopsy-to-prostatectomy and impaired pathological results or risk of BCR (15).…”
Section: Discussionmentioning
confidence: 99%
“…Further potential reasons for delayed treatment include patient's anxiety, desire to obtain more detailed information regarding therapeutic options, necessity for treatment of comorbidities or limited surgical capacities and long waiting lists. Most studies show no influence of the time from diagnosis to surgery of low or intermediate risk prostate cancer on the oncological outcome (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). However, a recent Canadian multicentre study observed a higher risk FIGURE 1 | Inclusion-and exclusion criteria for our study of patients undergoing immediate (≤3 months) vs. delayed (>3 and <6 months) radical prostatectomy for intermediate-or high-risk prostate cancer.…”
Section: Introductionmentioning
confidence: 99%